Landscape Structure Is a Major Driver of Bee Functional Diversity in Crops - Coutinho, Jeferson G. E.; Hipólito, Juliana; Santos, Rafaela L. S.; Moreira, Eduardo F.; Boscolo, Danilo; Viana, Blandina F. (Frontiers in Ecology and Evolution, 2021)
Land use change is having a negative effect on pollinator communities, and that changes in community structure may have unexpected impacts on the functional composition of those communities. Such changes in functional composition may impact the capacity of these assemblages to deliver pollination services, affecting the reproduction of native and wild plants. However, elucidating those relationships requires studies in multiple spatial scales since effects and consequences are different considering biological groups and interactions. In that sense, by using a multitrait approach we evaluated whether the landscape structure and/or local environment characteristics could explain the functional richness, divergence, and dispersion of bee communities in agroecosystems. In addition, we investigated to which extent this approach helps to predict effects on pollination services. This study was conducted in an agroecosystem situated in "Chapada Diamantina" region, State of Bahia, Brazil. Bees were collected using two complementary techniques in 27 sample units. They were classified according to their response traits (e.g. body size, nesting location) and effect traits (e.g means of pollen transportation, specialty in obtaining some resource). Our results indicate that both landscape heterogeneity and configuration matter in explaining the three properties of bee functional diversity. The Akaike Information Criterion (AIC) was used to select the best models created through the additive combination of landscape descriptors (landscape diversity, mean patch shape and local vegetation structure) at the local, proximal, and broad landscape levels. We indicate that functional diversity was positively correlated with compositional and configurational heterogeneity. These results suggest that landscape and local scale management to promote functional diversity in pollinator communities may be an effective mechanism for supporting increased pollination services.